2013
DOI: 10.1016/j.cbi.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

TRP and ASIC channels mediate the antinociceptive effect of citronellyl acetate

Abstract: The results of this work contribute information regarding the antinociceptive properties of CAT on acute pain and show that, at least in part, TRPV1, TRPM8, ASIC, glutamate receptors, PKC and PKA participate in CAT's antinociceptive mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…This might in part explain the lack of efficacy of SB-366791, capsazepine, and AMTB in our study, in which a relatively high concentration of formalin (5%) was used. Moreover, it must be emphasized that formalin-induced pain involves numerous mediators, channels, and receptors (Santos and Calixto, 1997;Coste et al, 2012), as well as nerve fiber types (Rios et al, 2013) and signaling pathways (Coste et al, 2012), so a selective inhibition of only one type of TRP channels might be insufficient to obtain effective antinociception. In addition, the local administration of TRP channel antagonists used in our study, and hence their strictly peripheral, local action might explain the lack of efficacy observed in the second phase of the test during which central sensitization of pain plays a pivotal role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might in part explain the lack of efficacy of SB-366791, capsazepine, and AMTB in our study, in which a relatively high concentration of formalin (5%) was used. Moreover, it must be emphasized that formalin-induced pain involves numerous mediators, channels, and receptors (Santos and Calixto, 1997;Coste et al, 2012), as well as nerve fiber types (Rios et al, 2013) and signaling pathways (Coste et al, 2012), so a selective inhibition of only one type of TRP channels might be insufficient to obtain effective antinociception. In addition, the local administration of TRP channel antagonists used in our study, and hence their strictly peripheral, local action might explain the lack of efficacy observed in the second phase of the test during which central sensitization of pain plays a pivotal role.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, nociception evoked by formalin and paclitaxel is not so clearly understood as it involves several distinct mechanisms. It was previously shown that formalin-induced pain is evoked by the activity of numerous mediators, channels, and receptors (Santos and Calixto, 1997;Coste et al, 2012), as well as nerve fiber types (Rios et al, 2013) and signaling pathways (Coste et al, 2012). Paclitaxel in turn is a chemotherapeutic agent, which causes toxic painful neuropathy and pain that are usually resistant to analgesic drugs (Nieto et al, 2012;Hara et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The odor of citronellol has previously been described as being sweet, rose-like (Hognadottir & Rouseff, 2003;Zhao et al, 2016), while citronellyl acetate, 2, has been reported to elicit a fresh, fruity smell associated with a lemon scent (Zhao et al, 2016). Due to their pleasant smell properties, 1 and 2 are fragrant compounds that are widely used in perfumes with citrus, floral notes (Bartsch, Uhde, & Salthammer, 2016;Rios et al, 2013). Owing to the chiral center at carbon 3, b-citronellol has two isomeric forms that both occur in nature.…”
Section: Introductionmentioning
confidence: 97%
“…2 is also present as major constituent in Corymbia citriodora (Rios et al, 2013). This plant, also known as Eucalyptus citriodora resin, has been demonstrated to be a potent antihepatoma agent with pro-apoptotic activity in HepG2 cells (human hepatoma cells); moreover, it also exerts antifungal, antibacterial and insect-repellent activity (Shen, Chen, & Duh, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…polyurethanes), and protect groups in organic synthesis [15][16][17][18]. N-methyl terpinyl carbamates are biologically active compounds due to their molluscicidal effect [19].…”
Section: Introductionmentioning
confidence: 99%